1989
DOI: 10.1073/pnas.86.22.8842
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of penicillin-binding protein genes in penicillin-resistant clinical isolates of Streptococcus pneumoniae.

Abstract: Resistance to penicillin in clinical isolates of Streptococcus pneumoniae has occurred by the development of altered penicillin-binding proteins (PBPs) that have greatly decreased affinity for the antibiotic. We have investigated the origins of penicillin-resistant strains by comparing the sequences of the transpeptidase domain of PBP2B from 6 penicillin-sensitive and 14 penicillin-resistant strains. In addition we have sequenced part of the amylomaltase gene from 2 of the sensitive and 6 of the resistant stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
257
1
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(273 citation statements)
references
References 27 publications
12
257
1
3
Order By: Relevance
“…Newer macrolidcs such as azithromycin, c1arithromycin are also ineffective in these isolates. Since it results from alteration of penicillin binding proteins, it is not surprising that cephalosporins are much less effective against penicillin resistant isolates [6]. The present isolatc was moderatcly resistant to penicillin (MIC Img/L) and resistant to fluoroqinolone norfloxacin besides resistant to other drugs e.g.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Newer macrolidcs such as azithromycin, c1arithromycin are also ineffective in these isolates. Since it results from alteration of penicillin binding proteins, it is not surprising that cephalosporins are much less effective against penicillin resistant isolates [6]. The present isolatc was moderatcly resistant to penicillin (MIC Img/L) and resistant to fluoroqinolone norfloxacin besides resistant to other drugs e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Overall this repre-" scnted a 12.6 fold increased incidence as compared to general population [5]. However in another study the incidence of pncumococcal bacteremia or meningitis is increased hundred fold in children who have sickle cell disease with splenic dysfunction [6]. The infection also spreads rapidly inside the body because spleen is the principal site of clearance of non-opsonised pneumococci from the blood stream due to the prolonged contact with reticuloendothelial cells while passing through the cords of Billroth and splenic sinuses [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multilocus enzyme electrophoresis (MLEE) has been applied to a number of bacteria, with the results generally suggesting that prokaryotes have clonal population structures (Selander et al, 1985(Selander et al, , 1987Piffaretti et al, 1989). Studies of the extent and pattern of DNA sequence diversity have been fewer in number, but have suggested that genetic exchange is more prevalent than the MLEE results might indicate (DuBose et al, 1988;Dowson et al, 1989). Thus, the most fundamental question concerns the extent of recombination among prokaryotes (Maynard Smith et al, 1991), which raises the question as to whether it is meaningful to discuss bacterial 'species'.…”
Section: Introductionmentioning
confidence: 99%